2019
DOI: 10.1002/hed.25766
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Chinese herbal medicine therapy for nasopharyngeal carcinoma: Clinical evidence and experimental validation

Abstract: Background To investigate the benefits of adjunctive Chinese herbal medicine (CHM) for patients with nasopharyngeal carcinoma (NPC). Methods We included all patients diagnosed with NPC during 1997‐2009 and followed until 2011 in Taiwan. We used 1:1 frequency matching by age, sex, comorbidity, conventional treatment, and index year to compare the CHM users and non‐CHM users (n = 2542 each). The prescribed CHM was further investigated with regard to its cytotoxicity. Results Compared with non‐CHM users, adjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
(85 reference statements)
3
11
0
Order By: Relevance
“…In a cohort of 784 patients with non-small cell lung cancer treated with platinum-based chemotherapy, 63 (8.0%) experienced thromboembolic events during treatment and their median overall survival was significantly shorter than those patients who did not have thrombolic events (9.5 vs. 12.9 months; p = 0.03) ( Mellema et al, 2014 ). Much evidence has shown that cancer patients using TCM have a significantly reduced risk of death ( Kuo et al, 2018 ), especially those with acute myeloid leukemia ( Tsai et al, 2017 ), chronic lymphocytic leukemia ( Fleischer et al, 2016 ), advanced breast cancer ( Lee et al, 2014 ), nasopharyngeal cancer ( Song et al, 2019 ), head and neck cancer ( Lin et al, 2015 ), lung cancer ( Shen & Wen, 2018 ), gastric cancer ( Hung et al, 2017 ), liver cancer ( Liao et al, 2015 ), pancreatic cancer ( Kuo et al, 2018 ), or metastatic prostate cancer ( Liu et al, 2016 ). Our data analysis has revealed a highly significant reduction in mortality risk among chemotherapy recipients who used TCM compared with those who did not, with Kaplan-Meier 5-year cumulative incidence mortality rates of 30 and 50%, respectively (Log-rank test, p < 0.0001); this mortality benefit with TCM persisted from the end of the second year of follow-up to the end of year 5.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 784 patients with non-small cell lung cancer treated with platinum-based chemotherapy, 63 (8.0%) experienced thromboembolic events during treatment and their median overall survival was significantly shorter than those patients who did not have thrombolic events (9.5 vs. 12.9 months; p = 0.03) ( Mellema et al, 2014 ). Much evidence has shown that cancer patients using TCM have a significantly reduced risk of death ( Kuo et al, 2018 ), especially those with acute myeloid leukemia ( Tsai et al, 2017 ), chronic lymphocytic leukemia ( Fleischer et al, 2016 ), advanced breast cancer ( Lee et al, 2014 ), nasopharyngeal cancer ( Song et al, 2019 ), head and neck cancer ( Lin et al, 2015 ), lung cancer ( Shen & Wen, 2018 ), gastric cancer ( Hung et al, 2017 ), liver cancer ( Liao et al, 2015 ), pancreatic cancer ( Kuo et al, 2018 ), or metastatic prostate cancer ( Liu et al, 2016 ). Our data analysis has revealed a highly significant reduction in mortality risk among chemotherapy recipients who used TCM compared with those who did not, with Kaplan-Meier 5-year cumulative incidence mortality rates of 30 and 50%, respectively (Log-rank test, p < 0.0001); this mortality benefit with TCM persisted from the end of the second year of follow-up to the end of year 5.…”
Section: Discussionmentioning
confidence: 99%
“…In ancient China, GLY was reportedly used to treat various conditions [33,34]. Recent research has investigated the potential benefits of using GLY as an adjuvant therapy in patients with throat disease by utilizing large-scale clinical databases and laboratory trials (n = 2542) [35]. It has been shown that patients with CP who are treated with GLY have a lower mortality and higher survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…The insoluble materials were removed by centrifugation at 3,000 rpm for 30 min and stored at 4 • C. Extracts were dissolved in water at a concentration of 100 mg/ml and stored at −20 • C until use. The method of preparation of CHM extract was described previously (9,13). The HPLC profile of BHSSC is shown in Figure S1.…”
Section: Preparation Of Chinese Herbal Medicine Extractmentioning
confidence: 99%
“…Some studies have demonstrated that CHM may enhance antitumor activity through increasing tumor apoptosis (7)(8)(9), inhibiting angiogenesis (10), and modulating the tumor microenvironment (11). In a large-scale clinical analysis, patients with malignant tumors who sought adjunctive CHM treatment had a better overall survival rate than patients who did not undergo CHM treatment (9,(12)(13)(14). Among frequently used forms of CHM, Hedyotis diffusa Willd (Bai Hua She She Cao, BHSSC) is associated with a reduced hazard ratio for mortality risk in nasopharyngeal carcinoma and breast cancer (9,12,14).…”
Section: Introductionmentioning
confidence: 99%